Proceedings of the Ninth ACM International Conference on Interactive Tabletops and Surfaces 2014
DOI: 10.1145/2669485.2669507
|View full text |Cite
|
Sign up to set email alerts
|

SleeD

Abstract: We present SleeD, a touch-sensitive Sleeve Display that facilitates interaction with multi-touch display walls. Large vertical displays allow multiple users to interact effectively with complex data but are inherently public. Also, they generally cannot present an interface adapted to the individual user. The combination with an arm-mounted, interactive display allows complex personalized interactions. In contrast to hand-held devices, both hands remain free for interacting with the wall. We discuss different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In a conventional wristwatch-type device, the display area is limited and fixed, namely the watch face. Flexible and curved display devices [30,33] expand display area from a portion on the wrist to whole circumference of the forearm [6,39,42]. Snaplet [39] is a sensoraugmented flexible display device that can detect the shape of the display, e.g., convex and flat, and offers different interactions depending on the shape.…”
Section: Interaction On the Arm And Handmentioning
confidence: 99%
See 2 more Smart Citations
“…In a conventional wristwatch-type device, the display area is limited and fixed, namely the watch face. Flexible and curved display devices [30,33] expand display area from a portion on the wrist to whole circumference of the forearm [6,39,42]. Snaplet [39] is a sensoraugmented flexible display device that can detect the shape of the display, e.g., convex and flat, and offers different interactions depending on the shape.…”
Section: Interaction On the Arm And Handmentioning
confidence: 99%
“…Snaplet [39] is a sensoraugmented flexible display device that can detect the shape of the display, e.g., convex and flat, and offers different interactions depending on the shape. SleeD [42] is a touch-sensitive sleeve display that facilitates explicit interaction with a wall-type display. DisplaySkin [6] is a whole-wrist circumference display that is flexible [30], and aims at realize implicit interactions with the user by adjusting the position and the orientation of displayed information to the forearm posture relative to the shoulder.…”
Section: Interaction On the Arm And Handmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be used to select and navigate con- tent at different scales [PNB09] or transfer and arrange information and data objects from a distance [CNS * 14, LvZH * 16]. User interface items on the mobile device may further be used to manipulate content and set parameters [vZBLD14]. These elements can be sketched [TBJ15] or applied as tangible objects [JDF12] that even allow eyes-free control of the view on the wall-sized display.…”
Section: Mobile Devices and Spatial Interactionmentioning
confidence: 99%
“…Jarusriboonchai et al [16] have demonstrated a social use case, where a neck-worn information display is aimed to facilitate co-located social interaction. Von Zadow et al [31] have demonstrated a sleeve with a display. Moreover, Schneegass et al [27] have presented a design space for onbody displays, and also an ambient communication display on a bracelet has been suggested [29].…”
Section: Related Work Locating Interaction Devices On Body and Accessmentioning
confidence: 99%